ORGANIZATION AND QUALITY OF MEDICAL AND REHABILITATION CARE FOR ACUTE MYOCARDIAL INFARCTION IN THE CONTEXT OF PUBLIC HEALTH - Ivan I. Koshelia (Клінічна та профілактична медицина)
Introduction. Acute myocardial infarction (AMI) remains one of the leading causes of mortality in Ukraine, despite healthcare reforms and the development of reperfusion care. High hospital mortality and limited rehabilitation coverage highlight the need for a systemic revision of treatment and recovery approaches.